Dual Inhibition of BMP and WNT Signals Promotes Pancreatic Differentiation from Human Pluripotent Stem Cells. (1st December 2019) - Tan, Mengtian; Jiang, Lai; Li, Yinglei; Jiang, Wei
Abstract : Pathological or functional loss of pancreatic beta cells is the cause of diabetes. Understanding how signaling pathways regulate pancreatic lineage and searching for combinations of signal modulators to promote pancreatic differentiation will definitely facilitate the robust generation of functional beta cells for curing hyperglycemia. In this study, we first tested the effect of several potent BMP inhibitors on pancreatic differentiation using human embryonic stem cells. Next, we examined the endodermal lineage bias upon potent BMP inhibitor treatment and further checked the crosstalk between signal pathways governing endodermal lineage determination. Furthermore, we improved current pancreatic differentiation system based on the signaling pathway study. Finally, we used human-induced pluripotent stem cells to validate our finding. We found BMP inhibitors indeed not only blocked hepatic lineage but also impeded intestinal lineage from human definitive endoderm unexpectedly. Signaling pathway analysis indicated potent BMP inhibitor resulted in the decrease of WNT signal activity and inhibition of WNT could contribute to the improved pancreatic differentiation. Herein, we combined the dual inhibition of BMP and WNT signaling and greatly enhanced human pancreatic progenitor differentiation as well as beta cell generation from both embryonic stem cells and induced pluripotent stem cells. Conclusively, our present work identified the crosstalk between the BMP and WNT signal pathways during human endoderm patterning and pancreas specification, and provided an improved in vitro pancreatic directed differentiation protocol from human pluripotent stem cells.